The Need for Digital Health Solutions in Deep Brain Stimulation for Parkinson's Disease in the Time of COVID‐19 and Beyond. Issue 2 (10th November 2020) - Rammo, Richard; Gostkowski, Michal; Rasmussen, Peter A.; Nagel, Sean; Machado, Andre
Abstract: Objectives: Deep brain stimulation (DBS) is a well‐established therapy for the management of patients with advanced Parkinson's disease and other movement disorders. Patients implanted with DBS require life‐long management of the medical device as well as medications. Patients are often challenged to frequently visit the specialized DBS centers and such challenges are aggravated depending on geography, socioeconomic factors, and support systems. We discuss the need for digital health solutions to overcome these barriers to better and safely take care of patients, especially in the current COVID‐19 pandemic. Materials and Methods: A review of the literature was conducted for technology and logistics necessary in forming a digital health program. Results: Digital health encounters can take place in both a synchronous and asynchronous manner. Factors involving patients include cognitive capacity, physical safety, physical capacity, connectivity, and technological security. Physician factors include examining the patient, system diagnostics, and adjusting stimulation or medications. Technology is focused on bridging the gap between patient and physician through integrating the DBS lead, implantable pulse generator (IPG), programmer, novel devices/applications to grade motor function, and teleconference modalities. Conclusions: For patients with Parkinson's disease, digital health has the potential to drastically change the landscape after DBS surgery. Furthermore, technology is fundamental in connectivity, diagnostic evaluation, and security in order to create stable and useful patient‐focused care.